Pathways into homelessness and perspectives on prevention: A qualitative study of army veterans - Katherine A. Koh; Jenny D’Olympia; Dina Hooshyar; Ana-Maria Vranceanu; Sara Garde; Zachary Ginsburg; Kelly Ré; Michaela Spaulding; James A. Naifeh; Matthew K. Nock; James Wagner; Robert J. Ursano; et al. (PLoS ONE, 2026)
Background Despite a national focus on ending veteran homelessness, many veterans remain homeless in the United States. Little qualitative research has explored in national samples the pathways that lead to homelessness among veterans or veteran perspectives on homelessness prevention. Methods We conducted individual semi-structured interviews with 55 US Army veterans from the national Army Study to Assess Risk and Resilience in Servicemembers-Longitudinal Study (STARRS-LS) who reported having an episode of homelessness after separating from the Army. Interviews included questions about their pathways into homelessness and what could have prevented their homelessness. Interview transcripts were analyzed for themes using a hybrid deductive-inductive approach. Results We identified three main themes as pathways into homelessness: (1) financial challenges while reintegrating into civilian life , including the subthemes of difficulty finding adequate employment and lengthy processing of VA disability benefits; (2) planning challenges around the transition, including the subthemes of lack of awareness of existing resources and personal challenges with planning; and (3) interpersonal disruptions upon reintegration , including the subthemes of loss of a primary relationship and intersections between social disruptions and having a mental illness. Notably, many participants identified connections between multiple themes as leading to homelessness after service. Veterans expressed that enrolling veterans in services prior to separation, decreasing barriers to receiving VA disability benefits, and enhancing access to mental health care would have helped prevent their homelessness. Conclusion The multiple challenges veterans identified as leading to homelessness most often began during the immediate transition period from the US Army to civilian life and are modifiable. These findings can be used to develop or enhance systems to improve prevention of homelessness among veterans.